The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5296/jse.v5i3.8109
|View full text |Cite
|
Sign up to set email alerts
|

Turkish Student’s Perception about the Black Body Radiation, Photoelectric Effect and Compton Scattering Phenomena

Abstract: The goal of this study is to research Turkish student's perception in the black body radiation, photoelectric effect and compton scattering phenomena. 26 11th grade students receiving education at a Turkish high school participated in the study. The black body radiation, photoelectric effect and compton scattering subjects were carried out throughout a 4 week period in 16 academic hours in accordance with the constructivist learning theory. 7 open-ended questions were applied as pre-study and post-study. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Many techniques to teach this topic have been developed by many researchers (Edmonds, 1968;Carvalho and Sousa, 2006;Lopresto and Hagoort, 2011;Marr and Wilkin, 2012;Sadoglu, 2015) and they revealed that students who had been taught via tradition teaching have many misconceptions such as students describe color as representative of the object temperature (Carvalho and Sousa, 2006), students always describe the blackbody as an object that has a dark color (Sadoglu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many techniques to teach this topic have been developed by many researchers (Edmonds, 1968;Carvalho and Sousa, 2006;Lopresto and Hagoort, 2011;Marr and Wilkin, 2012;Sadoglu, 2015) and they revealed that students who had been taught via tradition teaching have many misconceptions such as students describe color as representative of the object temperature (Carvalho and Sousa, 2006), students always describe the blackbody as an object that has a dark color (Sadoglu, 2015).…”
Section: Introductionmentioning
confidence: 99%